Contratações públicas como indutoras ao desenvolvimento econômico regional: um estudo com empresas do município de mossoró/rn - Diniz, Isac Dantas (Universidade Federal Rural do Semi-Árido, 2019)
The main objective of this work was to analyze the participation of the companies located in the municipality of Mossoró / RN, in public tenders carried out by federal government agencies located in their region, in order to identify the factors that hinder or discourage the participation of companies in the public contracting market. The study has a qualitative approach, using triangulation in data collection through observation, documental analysis and interviews. Therefore, we used descriptive statistics and the content analysis method to analyze the data collected. The secondary data collection stage was performed through bibliographic research, as well as documentary research, with data extracted from the Purchasing Panel of the Federal Government. In the case of primary data, the collection took place through interviews with companies that sell agricultural inputs and equipment, based in the municipality of Mossoró / RN. It was verified that despite the advances brought by electronic purchasing platforms, regarding transparency and publicity in public contracting of the federal government, as well as the increase of specific legislations that deal with incentives for the participation of micro and small local companies in these hirings, these actions did not foster the participation of local entrepreneurs in the public contracting of the federal government in a satisfactory and effective way
Keywords: Contratações Públicas; Política Pública; Preferência nas Contratações; Desenvolvimento Regional; Public Contracting; Public policy; Preference in Contracts; Regional development; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA